CULTURAL VALUES AND INQUIRY IN DEVELOPING EDUCATION AND CULTURE IN BANTAENG REGENCY, SOUTH SULAWESI - Hasanuddin Hasanuddin (Hasanuddin University, 2018)
Bantaeng is one of regencies in southern tip of South Sulawesi Province. This region possesses human cultural history which begun since prehistorical era around 4,700 years ago. Various cultural remains, mainly prehistoric and Islamic era down to colonial era, were found in this region. This study aims to reveal contained grand values of archaeological resources, as a guidance and or as an educational material. This study employed analytical description method to uncover various aspects and important values contained in archaeological resources of Bantaeng. Research regarding the cultural values of Bantaeng had been formulated and transformed as important values for educational, historical, cultural and religious purposes. These important values need to be inherited to young generation through educational media as an enrichment of national mental-spiritual education material, raising their awareness and pride of their nation’s civilization history and in the end strengthening their national personality and identity as much as their self concept of Indonesia as a nation.